The impact of spirituality on blood glucose control among patients with type 2 diabetes mellitus in Padangsidimpuan - Adi Antoni; Abdullah AA; Anto J. Hadi; Nur Hamdani Nur (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Diabetes mellitus (DM) is a chronic degenerative disease that requires lifelong management. Beyond biological, psychological, and social needs, spirituality is an essential dimension for individuals with chronic conditions. The number of individuals with diabetes in Padangsidimpuan has steadily increased, creating a burden on health services. This study aimed to explore the role of spirituality in the lives of patients with type 2 DM. A qualitative design with a phenomenological approach was applied, involving seven Muslim participants who met the inclusion criteria of no cognitive impairment, diagnosis for at least five years, a minimum bachelor’s education, and the ability to communicate effectively. The study was conducted in Padangsidimpuan from January to February 2025. Data were collected through in-depth interviews using a structured guide and analyzed using Colazzi’s method assisted by Open Code software. Three major themes and seven subthemes emerged: (1) Spirituality as motivation to live with diabetes (lifelong journey, spiritual motivation, acceptance of illness); (2) Nature as God’s creation to relieve problems (healing power of water, nature as divine solution); and (3) Harmonious human relationships to stabilize blood glucose (peace through social interaction, charity for better control). In conclusion, spirituality played a positive role in providing motivation, reinforcing life’s meaning, and fostering harmonious relationships with oneself, others, and the environment, thereby supporting better blood glucose control in patients with DM.